Methyl orange adsorption from aqueous solution by activated carbon: effect of Potassium Hydroxide (KOH) treatment - Ab Ghani, Nur Atikah (2018)
Water is important to the ecosystem for energy requirement to stay alive. Nowadays, rapid development in technology can cause pollution to the environment such as water quality pollution, and then faced by society. Dangerous source in wastewater such as dyes poses a severe problem due to its toxicity and it was hard to treat. Based on the absorption ability, activated carbon from corn cob was made for the removal of dyes in wastewater treatment. Activated carbon from corn cob was developed by using alkaline solution treatment of potassium hydroxide (KOH) with difference mass ratios, and then was characterized by using Fourier Transform Infrared, X-ray diffraction and scanning electron microscopy. The synthesized activated carbon was also used for removal of methyl orange from aqueous solution by using UV-Vis spectrophotometer. In this research, the obtained char yield after pre-carbonization at 500°C was 74.20%, while activated carbon yields were between 53.60% to 78.80%, based on its difference mass ratios of KOH. The activated carbon without an activation agent gave adsorption capacities of 14.63%. However, when the char was introduced to KOH, the adsorption was increased at the range of 41.09% to 80.36%. The percentage of dye removal increased when the mass ratios of KOH increased. The produce activated carbon from corn cob by using KOH can be effectively used for wastewater treatment.